2005
DOI: 10.1128/jcm.43.7.3341-3345.2005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Virulent Methicillin-Resistant Staphylococcus aureus Strains Carrying Panton-Valentine Leucocidin Genes in The Netherlands

Abstract: Methicillin-resistantMethicillin-resistant Staphylococcus aureus (MRSA) infections have been recognized for decades as hospital acquired or healthcare associated (2,6,20). Nowadays, MRSA is also recognized as a worldwide emerging community-acquired pathogen (CA-MRSA) (5, 30, 32). CA-MRSA generally causes primary skin and soft tissue infections, such as furunculosis and abscesses, but necrotizing tissue infections and lethal hemorrhagic pneumonia, even in previously healthy individuals, have recently been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
4
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 35 publications
6
67
4
6
Order By: Relevance
“…RIVM cluster 28 strains were first reported in The Netherlands in 1995. Multilocus sequence typing revealed that MRSA with PFGE cluster 28 belong to sequence type 80 (16,17). All isolates in the present study were positive for the S. aureus Panton-Valentine leucocidin (PVL) toxin genes (lukS-PV and lukF-PV) by PCR, performed as described by Lina et al (6).…”
Section: Case Reportmentioning
confidence: 75%
See 2 more Smart Citations
“…RIVM cluster 28 strains were first reported in The Netherlands in 1995. Multilocus sequence typing revealed that MRSA with PFGE cluster 28 belong to sequence type 80 (16,17). All isolates in the present study were positive for the S. aureus Panton-Valentine leucocidin (PVL) toxin genes (lukS-PV and lukF-PV) by PCR, performed as described by Lina et al (6).…”
Section: Case Reportmentioning
confidence: 75%
“…This virulence factor is associated with skin and soft-tissue infections such as furunculosis and abscesses as well as with severe necrotizing pneumonia in humans and has been found in community-acquired MRSA (CA-MRSA) infection in many countries (3,4,16,17). Outbreaks of PVL-positive CA-MRSA infection have been reported from closed living communities (jail inmates, military recruits, and gay men) and also among health care staff and within families (17). PVL-positive CA-MRSA strains often afflict relatively young persons without apparent risk factors (3,17).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported in 5 % by Holmes et al 29 . Higher detection of pvl -15 % of MRSA collected in 2002 -was described by Wannet et al 30 . No MRSA isolate with pvl in studied group is delectable information, because of present spread of these dangerous MRSA clones in the Czech Republic.…”
mentioning
confidence: 75%
“…Although no data were available for African countries, it could be anticipated that the frequency of such infections might be that higher. S. aureus resistance to methicillin became a worldwide problem (Wanne et al, 2005). Nowadays treatment focused on vancomycin.…”
Section: Discussionmentioning
confidence: 99%